2018
DOI: 10.1016/j.neubiorev.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Joggin’ the Noggin: Towards a Physiological Understanding of Exercise-Induced Cognitive Benefits

Abstract: This narrative review examines literature pertaining to possible physiological explanations for observed cognitive benefits stemming from improvements to cardiovascular fitness following chronic aerobic exercise. Studies regarding exercise and cardiovascular fitness, angiogenesis, neuroinflammation in relation to IGF-1 signalling, regulation of neurotrophins, neurogenesis and plasticity, cognitive training, are briefly described. We propose that current evidence points towards a mechanism by which cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 139 publications
4
105
1
2
Order By: Relevance
“…In this regard, physical fitness (PF) needs to be considered. PF is a measure of physical condition and well-being, and it has been reported that PA with an effective improvement in cardiovascular fitness has a greater effect on cognitive function than PA focused on strength 26 . We aimed to investigate the relationship between PA and PF with cognitive function and quality of life, independently of the impact of the adherence to an energy-restricted MedDiet, using baseline data from the PREDIMED-Plus trial 27 .…”
mentioning
confidence: 99%
“…In this regard, physical fitness (PF) needs to be considered. PF is a measure of physical condition and well-being, and it has been reported that PA with an effective improvement in cardiovascular fitness has a greater effect on cognitive function than PA focused on strength 26 . We aimed to investigate the relationship between PA and PF with cognitive function and quality of life, independently of the impact of the adherence to an energy-restricted MedDiet, using baseline data from the PREDIMED-Plus trial 27 .…”
mentioning
confidence: 99%
“…At first glance, our behavioural results are somewhat surprising, as a substantial body of clinical and preclinical literature has established positive behavioural effects of exercise in both WT mice and transgenic mouse models Stimpson et al, 2018;Suo et al, 2016). Furthermore, extensive research has established CA1 LTP and neurogenesis as candidate mechanisms underpinning enhanced cognitive functioning in WT and transgenic mice following exercise (Ohline & Abraham, 2018;Patten et al, 2015).…”
Section: Limitations and Conclusionmentioning
confidence: 88%
“…In rodents, the G × E interaction approach has been more successful due to experimental control over the environment (Nithianantharajah & Hannan, 2006). Voluntary physical activity (exercise) has been found to improve cognition in human and animal models (Stimpson, Davison, & Javadi, 2018;Suo et al, 2016). Additionally, exercise is known to enhance hippocampal synaptic plasticity and adult neurogenesis, although the precise mechanisms remain unclear (Ohline & Abraham, 2018;Patten et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the brain structure deteriorates in ageing with the prefrontal and medial temporal lobes being the most vulnerable areas , there is some evidence that maintaining fitness help counteract the functional effect of brain ageing. Potential mechanisms for this association are supported by animal studies and include exercise‐induced neurogenesis, endothelial cell proliferation, vascularization, neurotransmitters and neurotrophic factors . Whether maintaining fitness counteracts brain ageing in community‐dwelling older adults remains unclear because of the limited availability of longitudinal studies adequate to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%